Application of the orthogonal design method in geotechnical parameter back analysis for underground structures - Tian, Hongming; Chen, Weizhong; Yang, Diansen; Dai, Yonghao; Yang, Jianping (Bulletin of engineering geology and the environment, 2016)
The back analysis method has been widely used as an indirect method of determining geotechnical parameters based on field measurements. The number of parameters and their initial values greatly influence the reliability and efficiency of back analysis. Therefore, sensitivity analysis is often employed to select high sensitivity parameters that have more greater impact on measured back analysis values. The orthogonal design method was first utilized to select geotechnical parameters for back analysis. The optimized parameter values obtained from an orthogonal design table can be used as the initial back analysis values, so as to avoid optimisation algorithm searching in local parameter spaces. By introducing a penalty function to the objective function, back analysis of the geotechnical parameters is changed into an unconstrained optimisation problem, whereby the Nelder–Mead method can then be employed. To verify the feasibility of the proposed back analysis method, a case study was conducted to determine the rock mass parameters for the Houziyan underground powerhouse complex.